Electrochemically Modified Activated Carbon Fiber for the Removal of Uranium Ions - Jung*, Chong-Hun; Lee, Yu-Ri; Moon, Jei-Kwon; Won, Hui-Jun; Lee, Kune-Woo (Asian Journal of Chemistry, 2011)
The electrosorption of U(IV) from wastewater was carried out by using an activated carbon fiber felt electrode in a continuous electrosorption cell. Pore structure and functional groups of the activated carbon fibers electrochemically modified in an acidic or a basic solution were examined. It is believed electrosorption capacity is not affected by a surface acidity and the specific surface area of activated carbon fiber. The applied negative potential increased the adsorption capacity in comparison to an open circuit potential adsorption for uranium ions. The electrosorption amount of U(IV) on the base modified activated carbon fiber electrode at -0.3 V corresponds to that of the as-received activated carbon fiber electrode at -0.9 V. Such a high adsorption capacity on the base modified activated carbon fiber electrode probably was caused by the uranium precipitation on activated carbon fiber surface due to an increase of the hydroxyl by the base modification of activated carbon fiber.